Evaluation of the oil flow using the MQL technique applied in the cylindrical plunge grinding of AISI 4340 steel with cbn grinding wheel - Francelin, Rafael Polato (2018)
Abstract The grinding process is defined as an abrasive cutting action of a tool known as grinding wheel, which is submitted to high rotations, promoting excellent finishing and accuracy in dimensions, respecting the parameters established in each project. During the machining, the cutting edges of the abrasive grains undergo wearing and this increases the contact surface of the tool with the workpiece, increasing the machining temperature and creating possibilities of damaging it. Therefore, it is necessary to use a cutting fluid, responsible for lubricating and cooling the cutting zone, removing the chips from the cutting region between the workpiece and the wheel, and even having an anticorrosive action. However, its composition causes contamination to the environment and to the operator. In face of the increasingly strict environmental laws, it has become necessary to search for new methods of cooling that are at least as effective as conventional one and economically practicable. Thus, the Minimum Quantity of Lubrication was developed as a mist of air and oil applied at high pressure, reducing drastically the use of contaminants. In this work, two oil flows were used for the MQL technique, 30 ml/h and 120 ml/h. The wheel used was a CBN (Boron Cubic Nitride) one, composed of synthetic grains and the workpiece, in a ring format, were produced in AISI 4340 steel quenched and tempered. It was observed from results that MQL can be applied in the industrial processes without losing piece quality.